Reformulating National Criminal Law for Protecting Child Victims of Cyberbullying Crimes - Iwan Fahmi; Fanny Tanuwijaya (Rechtenstudent, 2025)
The advancement of digital technology has led to the emergence of new types of crime, including cyberbullying, which often targets children as the most vulnerable victims. Indonesia currently lacks specific legal provisions that regulate cyberbullying as a criminal offense against children. This research aims to examine the effectiveness of existing legal protections and the urgency of reformulating a more specific criminal framework. Using a normative legal approach and comparative study with the Philippines and California (USA), the findings indicate the need for comprehensive legal reform in Indonesia to ensure better protection for children against digital violence. The study highlights how the absence of a clear definition and categorization of cyberbullying in Indonesian legislation creates legal uncertainty and hinders law enforcement. Meanwhile, experiences from the Philippines and California show that explicit regulations provide stronger preventive and punitive measures. Therefore, reformulating a progressive legal framework that integrates criminal, civil, and administrative approaches is urgently needed to address the complexity of cyberbullying and safeguard children’s rights in the digital era.